2007
DOI: 10.1523/jneurosci.2255-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Transforming Growth Factor β1 Suppresses Inflammation and Promotes Survival in Adult CNS

Abstract: Transforming growth factor ␤1 (TGF␤1) is a pleiotropic cytokine with potent neurotrophic and immunosuppressive properties that is upregulated after injury, but also expressed in the normal nervous system. In the current study, we examined the regulation of TGF␤1 and the effects of TGF␤1 deletion on cellular response in the uninjured adult brain and in the injured and regenerating facial motor nucleus. To avoid lethal autoimmune inflammation within 3 weeks after birth in TGF␤1-deficient mice, this study was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 69 publications
(82 reference statements)
5
99
1
Order By: Relevance
“…Furthermore, TGF-b1 pathway blockers efficiently blocked epileptogenesis in BBB breakdown and albumin models of epilepsy in mice and rats (11,16). Although TGF-b1 is a well-characterized immunoregulatory cytokine (19,20,25,(31)(32)(33)(34), it can also exert autoimmunity, glial activation, and brain inflammation (22,23,35,36). In the present study, we demonstrate that glial exposure to TGF-b1 induces a rapid and robust IL-6 upregulation at both the mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, TGF-b1 pathway blockers efficiently blocked epileptogenesis in BBB breakdown and albumin models of epilepsy in mice and rats (11,16). Although TGF-b1 is a well-characterized immunoregulatory cytokine (19,20,25,(31)(32)(33)(34), it can also exert autoimmunity, glial activation, and brain inflammation (22,23,35,36). In the present study, we demonstrate that glial exposure to TGF-b1 induces a rapid and robust IL-6 upregulation at both the mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 57%
“…Initial studies by Beyth et al [50] and Maccario et al [28] noted the induction of cells with phenotypic characteristics of Treg but did not involve functional studies of suppression. Li et al have shown similar findings using placental-derived multi-potent stem cells [51]; this observation is interesting, as it again highlights the similarities between immunomodulation at the feto-maternal interface [39] and those operating during repair [52][53][54].…”
Section: Discussionmentioning
confidence: 58%
“…Increasing evidence suggests that astrocytes play a central role in CNS functioning by regulating the immune responses under pathological conditions (3). Astrocytes behave differently in terms of the secretion of neurotrophic factors or inflammatory mediators under physiological and pathological conditions (51,52). Activation of astrocytes following CNS injury may have beneficial effects that include the monitoring and controlling of the extracellular water, pH, and ion homeostasis to promote the repair process.…”
Section: Discussionmentioning
confidence: 99%